Taking into account students' psychotypes and using their neuropsychological maps when implementing digital educational technologies within the Metaverse - Galiya Ldokova; Svetlana Frumina; Suad Abdalkareem Alwaely (Smart Learning Environments)
Abstract The aim of the study is to examine the influence of students' psychotypes on their learning using digital educational technologies within the Metaverse. In the course of the longitudinal experimental study, the results of the initial testing of 79 students during their undergraduate studies and the re-testing of 75 of these students during their graduate studies were compared. To determine the students' psychotype, the Questionnaire of Character Accentuations, the Methodology for Determining the Dominant Hemisphere of the Brain and the Type of Interhemispheric Asymmetry, the Methodology for Diagnosing the Volitional Potential of an Individual, the Individual-Typological Questionnaire, and the Methodology for Determining the Structure of Temperament were used. The results of the psychodiagnostic testing were compared with the data of electroencephalography (EEG) neuroimaging. The following statistical methods were used to analyze the research results: Student's t-test, ANOVA analysis of variance, and Pearson's correlation coefficient. As a result of studying the features of the neuropsychophysiological profile of students, a persistent predominance of such character traits as anxiety, excitability, cyclothymia, and emotional sensitivity was revealed. A relationship was demonstrated between students' personality psychotypes, their neuropsychological profiles, and the success of their learning outcomes. It was revealed that learning using digital online technologies in the context of the Metaverse has a positive effect on the development of the mobility of neural processes, and cognitive and psychophysiological mechanisms, increases the involvement and motivation of students to acquire new knowledge, helps to normalize the balance between the psychophysiological processes of excitation and inhibition, activates the areas of the cerebral cortex responsible for will, emotions, self-awareness, motivation and communication, contributes to the development of communicative competence, critical thinking and creative potential of the student's personality. The scientific contribution of the authors is to confirm the relationship between the students' psychotype, the dominant activity of the brain lobes, and the level of academic success, which substantiates the positive significance of individualization of learning based on the introduction of virtual and augmented reality technologies into the educational process in higher education institutions. The results of the study can be used to optimize and increase the efficiency of the educational process through the implementation of Metaverse technologies. The study of the influence of gender and age-related psychophysiological characteristics of an individual on his or her learning ability in the context of andragogy is considered a promising direction of research.